Implementation of physiotherapy telerehabilitation before and post Covid-19 outbreak: A comparative narrative between South American countries and Australia - Antonio Michell; Manuela Besomi; Pamela Seron; Matías Voigt; Rodrigo Cubillos; Felipe Parada-Hernández; Oscar Urrejola; Thaiana Barbosa Ferreira-Pacheco; Danilo de Oliveira-Silva; Jéssica Bianca Aily; Jorge Enrique Moreno-Collazos; Iván Darío Pinzón-Ríos; et al. (Instituto Nacional de Salud Pública, 2022)
The continuous development in telecommunication technologies has created opportunities for health professionals to optimise healthcare delivery by adopting digital tools into rehabilitation programs (i.e., telerehabilitation). These technological advances, along with the demographic and social characteristics of each country, have made the implementation of telerehabilitation a disparate process across regions. We have gathered the experience of four countries (Australia, Chile, Brazil, and Colombia) in two different regions (Oceania and South America) to recompile the history pre- and post-Covid-19 outbreak until January of 2021, the barriers to, and facilitators of telerehabilitation, and outline the future challenges for these countries.